MODEL PENGOLAHAN AIR GAMBUT MENJADI AIR MINUM BERBASIS MASYARAKAT - Kiswanto Kiswanto; Wintah Wintah; Nur Hafni; Maiza Duana (Journal of Aceh Aquatic Sciences, 2017)
Research about model of peat moss water processing become drinking water based on society is used to eliminate organic matter, chemical elements which are Fe, TDS, Zn, Flurida, NO3, and NO2 and pH. This model has purpose to find the solution about the supply of drinking water properly and simply to household and society. This research is conducted in Sub District Johan Pahlawano, West Aceh, exactly in the society surrounded by peat moss water area. This is experimental research which uses model of filtering tools of peat moss water, with the medias are sand, gravel, charcoal from coconut shell, then are filled in PVC pipe with up flow system. The samples are used 3 water samples from vary villages surrounded the circle of Teuku Umar University that contain peat moss waters, those are Cot Lawang, Rundeng and Seunebok. The research result with experimental method by Simple Plan from PVC pipe appropriates with Standard Work Of Clean Water for the parameter of Fe, TDS, Zn, Flurida, NO3, dan NO2 based on PERMENKES RI No. 907 of 2002. But for the pH, the result cannot reach that standard. So, it needs to improve the engineering model to reach the perfect result. Thus, the engineering tools can be applied in the society with water supply problem, especially in peat moss water area. However, this water result is only used to the need except as drinking water.